Early life programming by diet can play a role in risk reduction of otitis in dogs - Hemida, Manal B. M.; Vuori, Kristiina A.; Borgström, Nona C.; Moore, Robin; Rosendahl, Sarah; Anturaniemi, Johanna; Estrela-Lima, Alessandra; Hielm-Björkman, Anna (Frontiers in Veterinary Science, 2023)
A cross-sectional hypothesis-driven study with longitudinal data was performed to search for associations between pre-and postnatal exposures, and the incidence of owner-reported otitis in dogs at over one year of agelater in life. The study included 3064 dogs and explored 26 different early life variables at four early life stages: prenatal, neonatal, postnatal, and puppyhood in a multi-model design, for their potential association with owner-reported otitis incidence in dogs later in life. We compared two feeding patterns, a non-processed meat-based diet (NPMD) and an ultra-processed carbohydratebased diet (UPCD). A multivariate logistic regression analysis showed that having a mother that suffered from otitis and being an otitis-prone breed were both significantly associated positively with the incidence of developing otitis later in life. The maternal diet during pregnancy, the puppies' first solid diet, and the puppies' diet from 2 to 6 months of age were also associated with otitis incidence later in life. The NPMD was significantly associated with a lower risk while the UPCD was significantly associated with a higher risk of otitis incidence later in life. Furthermore, if the dog was born in the current family, was exposed to sunlight for more than one hour daily and was raised on a dirt or lawn floor during puppyhood, there were a lower risk of otitis development later in life. Additionally, the estimated impact of consuming different ratios of either NPMD or UPCD during puppyhood on the prevalence of owner-reported otitis within the study sample showed a significant Hemida et al.2 decrease in cases when consuming >25 % NPMD in their diet, while a significant increase in cases was seen when consuming >75 % UPCD in their diet. We conclude that the mother's consumption of NPMD during pregnancy, the puppy's first solid diet, and the puppy's diet from 2 to 6 months of age all were significantly associated with a decreased risk of owner-reported otitis development in dogs during adulthood at over one year of age. By contrast, the consumption of UPCD during the previously mentioned life periods were associated with a higher risk of otitis in adulthoodat over one year of